2018
DOI: 10.3389/fphar.2018.00740
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Inhibits Biofilm Formation by Staphylococcus xylosus and Affects Histidine Biosynthesis Pathway

Abstract: Staphylococcus xylosus, a coagulase-negative, non-pathogenic bacterium, responsible for opportunistic infections in humans and bovine mastitis, has the ability to form biofilms, which are responsible for persistent infections and antibiotic resistance. In our study, azithromycin significantly inhibited biofilm formation by altering protein expression. Of the 1764 proteins measured by the isobaric Tag for Relative and Absolute Quantification (iTRAQ) technique, only 148 proteins showed significantly different ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The connection between these lifestyle conditions and histidine metabolism has not been studied in B. subtilis , but it has been observed in A. baumannii , where histidine degradation was shown to be upregulated in proteomic studies of biofilms, and histidine supplementation stimulated increased biofilm production 37 . Two recent studies discovered that biofilm-inhibiting antimicrobials worked by suppressing histidine synthesis in Staphylococcus xylosus 38 , 39 . One proposed mechanism implicated the production of extracellular DNA, which is an important component of both A. baumannii and B. subtilis biofilms 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The connection between these lifestyle conditions and histidine metabolism has not been studied in B. subtilis , but it has been observed in A. baumannii , where histidine degradation was shown to be upregulated in proteomic studies of biofilms, and histidine supplementation stimulated increased biofilm production 37 . Two recent studies discovered that biofilm-inhibiting antimicrobials worked by suppressing histidine synthesis in Staphylococcus xylosus 38 , 39 . One proposed mechanism implicated the production of extracellular DNA, which is an important component of both A. baumannii and B. subtilis biofilms 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Gene Ontology (GO) serves as a crucial bioinformatics analysis method and tool for expressing various properties of genes and their products ( Milano, 2022 ). GO annotations are categorized into three groups: Biological Process, Molecular Function, and Cellular Component, providing insights into the biological roles of proteins from different perspectives ( Ding et al, 2018 ). The differential proteins obtained from the experiments underwent GO enrichment analysis, with the results depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report indicated that Azithromycin was effective at sub-MIC levels against Porphyromonas gingivalis biofilms and could be used for future clinical treatment for oral biofilm infections 17 which is similar to our finding. Similarly, Azithromycin is also a potential inhibitor of Staphylococcus xylosus biofilm formation by altering protein expression 18 .…”
Section: Discussionmentioning
confidence: 99%